(untitled) (Research, Society and Development, 2023)
Sporotrichosis is a zoonotic mycosis caused by fungi of the genus Sporothrix. The pathogen is present in soil, water, organic matter and composition, and is therefore found in different environments. However, although sapronotic transmission is possible, in Brazil this happens mainly due to traumatic inoculation of the fungus on the skin, from bites and scratches caused by infected cats. From then on, the disease can give rise to different clinical manifestations, mainly represented by cutaneous and behavioral signs, which can significantly compromise the health of the animal. Although the disease affects cats more often, dogs are also tolerant, but its diagnosis is often a challenge. Therefore, the objective of this article is to report a clinical case of intranasal sporotrichosis in a one-year-old German Spitz bitch, whose only sign was inspiratory dyspnea, unlike the manifestation that was more common. The diagnosis was defined based on the histopathological evaluation of the fragment obtained via rhinoscopy. The dog was treated with the antifungal itraconazole and there was complete remission of the disease. This study reinforces the need to establish the correct diagnosis and treatment for the patient, in addition to showing that sporotrichosis should be considered as a differential diagnosis in dogs with respiratory or cutaneous lesions.